Durable Capital Inputs: Conditions for Price Ratios to be Invariant to Profit-Rate Changes. A Comment on Professor Samuelson - Salvatore Baldone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1983)
In this note we intend to prove that the uniform capital intensity assumption is a general condition for relative prices to be invariant both in models with circulating capital only and in fixed capital models irrespective of machine-depreciation schedules.
Keywords: 330